Characteristics of sub-aerially emplaced pyroclasts in the Surtsey eruption deposits: implications for diverse Surtseyan eruptive styles - Verolino, Andrea (2023)
The 1963–1967 shallow-to-emergent eruption in Iceland’s Vestmannaeyjar earned a place in the history of volcanology by creating the island of Surtsey while under close observation of volcanologist Sigurdur Thorarinsson (Sigurður Þórarinsson in Icelandic). This is an example of what is now called Surtseyan volcanism, and it included explosive and effusive phases from multiple vents that formed the island of Surtsey itself, as well as one fully subaqueous pyroclastic edifice and two additional, but ephemeral, islands. Sigurdur Thorarinsson identified tephra jetting and continuous uprush as characteristic types of subaerial explosive activity of Surtseyan volcanism. Subaerial cone-forming deposits of Surtseyan volcanism are typically poorly sorted, with fine-grained beds rich in sideromelane ash fragments, punctuated by larger, ubiquitously composite bombs, whereas deposits sampled by coring deep into the submarine edifice include fines-poor horizons dominated by vesicular coarse sideromelane ash. Here, we present new textural data and highlight the diversity of pyroclasts and microtextures from Surtsey (Surtur I and Surtur II) and its satellite vents (Surtla, Syrtlingur and Jolnir), in the context of Surtseyan volcanism. We used several sample sets. Some were collected during the 3.5-year long eruption and were conserved in the Icelandic Natural History Museum, including one sample from the core drilled into Surtsey in 1979. Other samples were collected during more recent field campaigns on Surtsey Island. In closing, we discuss the implications of this diversity for the range of activity and products produced by Surtsey.